ORGANIZATIONAL AND PEDAGOGICAL CONDITIONS OF DEVELOPING INDEPENDENT KNOWLEDGE USING IT IN TEACHING STUDENTS IN INFORMATION SCIENCE - Kilichev Nurilla Abbosovich (American Journals, 2023)
This article describes the organizational and pedagogical conditions for the development of independent knowledge using an act in teaching informatics to students. It is also noted that there are a number of advantages of using ICT in educational activities, that the main functional characteristics of ICT provide certain opportunities in the educational process.
Keywords: IKT, education, nonlinear technologies, informatics, cognitive independence, information, development, principle, description, student, person.